Analysis of the needs of problem children towards the quality of life that is moral and characterized - Hadiwinarto Hadiwinarto; Herman Nirwana (International Journal of Research in Counseling and Education, 2019)
This study aims to describe problem children, with a sample of 52 child convicts. In-depth interview techniques with counseling approaches, focused discussions and questionnaires were used for data collection. Data analysis used content analysis techniques and descriptive analysis. This research is the result of the first year of research planned for three years. The results of the study show that: child convicts are in a critical age, a period of seeking identity; have a low education background; very rarely interact socially with their father and mother; Child convicts have various unmet needs in their families. Their needs include: psychological needs, physical needs, social needs, future needs, information needs, and the need to live in character and culture. It is recommended that the results of the first year research be used to determine the right education model for child convicts to lead a moral and characterized life.